Halide Versus Nonhalide Salts: The Effects of Guanidinium Salts on the Structural, Morphological, and Photovoltaic Performances of Perovskite Solar Cells. Issue 2 (26th July 2019) - Alotaibi, Mohammad Hayal; Alzahrani, Yahya A.; Arora, Neha; Alyamani, Ahmed; Albadri, Abdulrahman; Albrithen, Hamad; Al-Lehyani, Ibrahim H.; Alenzi, Sultan M.; Alanzi, Ali Z.; Alghamdi, Fahad S.; Zakeeruddin, Shaik M.; Meloni, Simone; et al.
Abstract : The impacts of halide and nonhalide sources of guanidinium cations, including guanidinium chloride (GCl) ((NH2 )3 CCl) and guanidinium thiocyanate (GTC) ((NH2 )3 CSCN), are comparatively analyzed on the structural, morphological, and photophysical properties of (CsMAFA)PbBr x I3 −  x ( x  = 0.17) (MA = methylammonium, FA = formamidinium) perovskite films. X‐ray diffraction (XRD) reveals that the formation of photoinactive phases depends on the nature of counterions (halide vs nonhalide). Furthermore, morphological analysis shows that with the addition of guanidinium salts, the apparent grain size decreases due to the enhancement of nucleation density and/or slow growth of perovskite structures. More importantly, the introduction of GCl leads to the fabrication of perovskite solar cells (PSCs), yielding a photovoltage as high as 1.16 V (1.1 V for reference). In contrast, the introduction of GTC minimally affects the photovoltage, underlining the significance of counterions in improving the photovoltage of PSCs. The present preliminary results of the density functional theory based theoretical investigation related to the effect of G cation on the structure of the perovskite system is presented. In summary, the insights gained through structural and morphological characterization helps to understand the critical role of counterions of guanidinium salts in PSCs. Abstract : Halide‐ and nonhalide‐based guanidinium salts are explored to study the impact of counterions supplied along with the guanidinium cation on the photophysical properties of perovskite films and photovoltaic performance of perovskite solar cells.